Anti-anaphylactic effects of Trichilia monadelpha (Thonn.) J. J. De Wilde extracts on rodent models of anaphylaxis - Inemesit Okon Ben; Eric Woode; George Asumeng Koffuor; Emmanuel Akomanin Asiamah (Wolters Kluwer Medknow Publications, 2016)
Effects of petroleum ether and ethanolic extracts of Trichilia monadelpha stem bark (PEE and EAE) on compound 48/80-induced systemic and passive anaphylaxis were determined. Survival rate, extravasation, degranulation of mast cells, and secretion of tumour necrosis factor-α (TNF-α) and interleukin-6 (IL-6) were measured after pre-treatment with extracts (10-100 mg/kg) and disodium chromoglycate (2.5-250 µg/kg) and induction of anaphylaxis in C57BL/6 mice or Sprague-Dawley rats with compound 48/80. Histopathological assessments were made from skin biopsies of rats. Data was analyzed by Kaplan-Meier Survival Log-Rank Analysis, or One-way ANOVA and Holm-Sidak's post hoc test. PEE and EAE inhibited (P ≤ 0.0001) tremors in systemic anaphylaxis passive cutaneous anaphylactic reactions and extravasation, stabilized or prevented (P ≤ 0.001-0.0001) mast cell degranulation, and inhibited (P ≤ 0.001-0.0001) TNF-α and IL-6 secretion. Per the findings, PEE and EAE of T. monadelpha have exhibited substantial anti-anaphylactic and anti-inflammatory property (with PEE performing better) which substantiates its use traditionally in management of allergies and other inflammatory disorders .